Linguistic Values Based Intelligent Information Processing: Theory, Methods, and Applications - Pei, Zheng; Ruan, Da.; Liu, Jun.; Xu, Yang.; SpringerLink (Online service) (Paris : Atlantis Press, 2010)
This book focuses on systematic and intelligent information processing theories and methods based on linguistic values. The main contents include topics such as the 2-tuple model of linguistic values, 2-tuple linguistic aggregation operator hedge algebras, complete hedge algebras and linguistic value reasoning, reasoning with linguistic quantifiers, linguistic reasoning based on a random set, the fuzzy number model of linguistic values, linguistic value aggregation based on the fuzzy number model, extraction of linguistic proposition from a database and handling of linguistic information on the Internet, linguistic truth value lattice implication algebras, linguistic truth value resolution automatic reasoning, linguistic truth value reasoning based on lattice implication algebra, and related applications in decision-making and forecast.
The 2-Tuple Fuzzy Linguistic Representation Model -- Hedge Algebras of Linguistic Values -- Linguistic Information Processing Based on Lattice Structrure -- Fuzzy Number Indexes of Linguistic Values -- Hierarchical Structure Analysis of Linguistic Values -- Conclusions and RelatedWorks.
Keywords: Computer science; Translators (Computer programs).; Computer Science; Language Translation and Linguistics